Children’s outdoor play at early learning and child care centres: Examining the impact of environmental play features on children’s play behaviour - Rachel Ramsden; Ian Pike; Sally Thorne; Mariana Brussoni (PLoS ONE, 2025)
Early learning and child care centres are critical settings to support children’s regular, repeated and quality time spent in outdoor play. Gibson’s theory of affordances highlights the importance of the human-environment relationship, emphasizing how children use environmental information to inform their behaviour. This study aims to understand the association between children’s outdoor play behaviour and common environmental play features in early learning and child care outdoor play spaces, through the behaviour patterns of children. Children’s play behaviour was collected via observational behaviour mapping at eight early learning and child care centres in the Greater Vancouver region between September 2021 and November 2022, as part of the PROmoting Early Childhood Outside study. A multivariate logistic regression model examined the association between outdoor play behaviour and environmental play features, via odds ratio and 95% confidence intervals. The results indicate environmental play features, including gardening areas, playhouses, climbing structures and tricycle paths supported increased opportunities for children’s outdoor play. Gardening areas, playhouses, sandboxes, outdoor stages and fixed water features provided opportunities for exploratory play, while climbing structures and trike paths provided opportunities for physical play. Opportunities for diverse forms of play were less realized in dedicated open play areas, with the availability of loose parts and moveable equipment primarily influencing these spaces. The results of this study have important implications for future early learning and child care outdoor space design. Further research should consider children’s dynamic movement and transition between outdoor affordances, and the influence of loose parts on the use of environmental play features.